2016
DOI: 10.1037/npe0000054
|View full text |Cite
|
Sign up to set email alerts
|

Neuroticism predisposes to donation more than agreeableness: An fMRI study.

Abstract: Using functional magnetic resonance imaging (fMRI) in study 1, we examined the effect of two personality dimensions related to altruism such as Agreeableness and Neuroticism on the neural response to videos including images of situations from developing countries and audios of sentences employed by NGOs to demand help. For all the participants, the brain response across the whole brain was not significantly different in the Donor and Control videos. Multiple regression analyses revealed that while Agreeablenes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…This null finding suggests that the relationship between neuroticism and job selection is more complex than expected. Although one line of research found that neuroticism was positively related to altruism and helping behavior (Ben‐Ner & Kramer, 2011; Pinazo et al, 2016), other scholars also found that neuroticism was negatively or even non‐significantly related to individuals' other‐regarding behavior (e.g., Habashi et al, 2016; Lönnqvist et al, 2011) and public‐sector employment (Korac et al, 2020). A possible explanation for the mixed results may be attributed to other mediation mechanisms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This null finding suggests that the relationship between neuroticism and job selection is more complex than expected. Although one line of research found that neuroticism was positively related to altruism and helping behavior (Ben‐Ner & Kramer, 2011; Pinazo et al, 2016), other scholars also found that neuroticism was negatively or even non‐significantly related to individuals' other‐regarding behavior (e.g., Habashi et al, 2016; Lönnqvist et al, 2011) and public‐sector employment (Korac et al, 2020). A possible explanation for the mixed results may be attributed to other mediation mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Empirical research has supported that P‐E fit is a critical link that influences the attractiveness of public sectors and personality as an essential trait sorting individuals into the public sector (Korac et al, 2019). The existing literature suggests that neuroticism is positively related to altruism and helping behavior (Ben‐Ner & Kramer, 2011; Pinazo et al, 2016). This is because individuals with high levels of neuroticism are more sensitive to others' negative emotions, which leads them to experience more stress than average (Guo et al, 2018).…”
Section: Theoretical Framework and Hypothesis Makingmentioning
confidence: 99%
“…Nostalgia proneness was also included, supported by Ford and Merchant's (2010) study, which demonstrated that individuals more prone to nostalgia displayed heightened donation intentions when exposed to personally meaningful nostalgic appeals. We also considered the Big Five personality traits, given the extensive body of literature linking these traits, particularly agreeableness and neuroticism, to donation behavior (e.g., Hill, 2016;Pinazo et al, 2016). Finally, we included an individual's perceived financial well-being, drawing from research indicating an association between financial capital and charitable giving (L. Wang & Graddy, 2008).…”
Section: Overview Of Current Researchmentioning
confidence: 99%